Validation of the prolapse quality of life questionnaire (P-QOL) in a Turkish population - AY, NADİYE PINAR (ELSEVIER IRELAND LTD, 2007)
Objective: To validate the Turkish translated version of the prolapse quality of life questionnaire (P-QOL). Study design: After establishing the test-retest reliability and internal consistency in a pilot study, 310 patients were enrolled in the study and general and subscale scores of the questionnaires were calculated. All participants underwent the International Continence Society (ICS) prolapse score (POP-Q). Results: One hundred and forty-five (49.7%) women were symptomatic and 147 (50.3%) were asymptomatic. The level of missing data ranged from 0 to 2.2%. For the test-retest reliability, Spearman's rho was from 0.91 to 1.00 for all domains (p < 0.001). The severity of PQOL was strongly correlated with the vaginal examination findings among the symptomatic group (p < 0.001). Items correlated with the objective vaginal examination findings. The total and domain scores for P-QOL of symptomatic and asymptomatic women were found to be statistically significant (p < 0.001). Conclusion: The Turkish translated version of the P-QOL is reliable, consistent and valid instrument for assessing symptom severity, impact on quality of life in women with uterovaginal prolapse. It is easy to understand may be easily administered and self-completed by the women. 2007 Elsevier Ireland Ltd. All rights reserved.
Keywords: urogenital prolapse; quality of life; validation; PELVIC ORGAN PROLAPSE; STANDARDIZATION; TERMINOLOGY